The European Central Bank: Building a shelter in a storm - Dae Woong Kang; Nick Ligthart; Ashoka Mody (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
As the financial crisis gathered momentum in 2007, the United States Federal Reserve brought its policy interest rate aggressively down from 5 1/4 percent in September 2007 to virtually zero by December 2008. In contrast, although facing the same economic and financial stress, the European Central Bank's first action was to raise its policy rate in July 2008. The ECB began lowering rates only in October 2008 once near global financial meltdown left it with no choice. Thereafter, the ECB lowered rates slowly, interrupted by more hikes in April and July 2011. We use the "abnormal" increase in stock prices - the rise in the stock price index that was not predicted by the trend in the previous 20 days - to measure the market's reaction to the announcement of the interest rate cuts. Stock markets responded favorably to the Fed interest rate cuts but, on average, they reacted negatively when the ECB cut its policy rate. The Fed's early and aggressive rate cuts established its intention to provide significant monetary stimulus. That helped renew market optimism, consistent with the earlier economic recovery. In contrast, the ECB started building its shelter only after the storm had started. Markets interpreted even the simulative ECB actions either as "too little, too late" or as signs of bad news. We conclude that by recognizing the extraordinary nature of the circumstances, the Fed's response not only achieved better economic outcomes but also enhanced its credibility. The ECB could have acted similarly and stayed true to its mandate. The poorer economic outcomes will damage the ECB's long-term credibility.
urn:nbn:de:hebis:30:3-392969
Keywords: 330